Wintering yearling steers on bluestem pasture, 1949-50. - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
The maximum utilization of bluestem pasture in keeping with sound management is of utmost importance to Kansas stockmen. If a system of wintering and grazing yearling steers can be developed to utilize bluestem grass profitably during the winter it will be a major contribution to the industry. The primary purpose of this study, then, is to test the value of dry bluestem pasture as a winter feed for yearling steers when fed different kinds and amounts of protein supplements.
Keywords: Beef; Bluestem pasture; Protein; Weight